Description of Leishmania species among dogs and humans in Colombian Visceral Leishmaniasis outbreaks (2018)
We report the species detected in dogs and humans from outbreaks of visceral leishmaniasis in Colombia. In this study, 91 sera from patients (n = 38) and dogs (n = 53) diagnosed with visceral leishmaniasis using IFAT were analyzed to determine the causative species. DNA extraction, PCR amplification, DNA sequencing and species identification was performed. Results were obtained with 13 of the sera. A phylogenetic tree and a network of haplotypes were constructed. Leishmania infantum chagasi (11/13), Leishmania braziliensis (1/13) and Leishmania amazonensis (1/13) were identified as the circulating species and genetic variability in one of the L. infantum chagasi strains was demonstrated. This is the first study describing Leishmania species in outbreaks of visceral leishmaniasis in Colombia. © 2018 Elsevier B.V.